2019
DOI: 10.1186/s12877-019-1065-7
|View full text |Cite
|
Sign up to set email alerts
|

Does aquatic exercise improve commonly reported predisposing risk factors to falls within the elderly? A systematic review

Abstract: Background According to the World Health Organization, the elderly are at the highest risk of injury or death from a fall. Age-related changes in strength, balance and flexibility are degenerative factors that may increase the risk of falling, and an aquatic training may offer a favourable environment to improve these modifiable risk factors. Methods A systematic review was conducted to assess the potential preventative role of aquatic exercise for reducing the risk of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 64 publications
1
17
0
4
Order By: Relevance
“…In particular, only two studies analyzed aquatic therapy [34,35], which seems to be an interesting alternative to land-based exercise for the geriatric population, permitting low-impact and low-weight-bearing exercise. In fact, Guillamon et al [52] presented some evidence that aquatic exercise can improve modifiable risk factors of falls, although the quality of this evidence was low, and there was a lack of consistency between studies. A limitation of this systematic review was the high variability of the training protocols of the included studies.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, only two studies analyzed aquatic therapy [34,35], which seems to be an interesting alternative to land-based exercise for the geriatric population, permitting low-impact and low-weight-bearing exercise. In fact, Guillamon et al [52] presented some evidence that aquatic exercise can improve modifiable risk factors of falls, although the quality of this evidence was low, and there was a lack of consistency between studies. A limitation of this systematic review was the high variability of the training protocols of the included studies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous systematic reviews have summarized empirical evidence for aquatic exercises on strength, mobility, flexibility, balance, and various health outcomes in older adults [12,13,17]. Observations from these reviews have indicated that aquatic exercises may improve the aforementioned outcome measures.…”
Section: Introductionmentioning
confidence: 99%
“…Aquatic exercises have been utilized as an alternative to land-based exercises for older adults that display lower physical activity levels, neuromuscular degeneration, or orthopedic disabilities that affect balance, mobility, and pain [ 12 14 ]. For this systematic review and meta-analysis, we defined the aquatic exercise as any type of exercise performed in water.…”
Section: Introductionmentioning
confidence: 99%
“…These aquatic activities have to do with the development of varied types of motor practices, which have to do with educational, competitive, utilitarian, recreational, preventive, therapeutic, training and maintenance objectives. 24. In general, these aquatic activities developed in aging populations provide a low-impact and lightweight environment where people can exercise safely, 12 where buoyancy, pressure, resistance and water temperature maximize the effectiveness of aquatic exercise, allowing light and safe body movements. 25 Regarding the protocols used, the 9 systematized studies have reported varied intensities, frequencies and durations of the intervention programs.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Currently, several studies have shown that physical activity programs based on aquatic exercise have produced significant positive changes in the functional fitness of older adults. [8][9][10][11] Therefore, it is necessary for aging populations to participate in these intervention programs to improve their levels of agility, balance, coordination, strength, flexibility and speed, 12 as well as, muscle power, respiratory muscle function, postural stability, and aerobic capacity. 13 Aquatic programs are defined as a set of exercises performed in water, mainly in upright position, with or without music, and in shallow or deep water, 14 or even involves any type of physical exercise that is practiced immersed in water.…”
mentioning
confidence: 99%